Total oxidation of model volatile organic compounds over some commercial catalysts - Matějová, Lenka; Topka, Pavel; Jirátová, Květuše; Šolcová, Olga (Applied catalysis. A, General, 2012)
[Display omitted] ► Three commercial catalysts tested in total oxidation of VOCs at lab scale. ► Cu–Mn/alumina the most active and selective in oxidation of ethanol. ► Pt–Pd/alumina the most suitable for toluene oxidation. ► Pt–Pd/alumina–ceria the most active in dichloromethane oxidation. ► The highest HCl yield achieved with Pt–Pd/alumina. Commercial VOC oxidation catalysts can be used as comparative materials during development of new or improved catalysts. The objective of this study was to investigate physicochemical properties of EnviCat® commercial catalysts and their performance in total oxidation of three model compounds (dichloromethane, toluene and ethanol) at laboratory scale. The reactivity of model VOC was decreasing in the order ethanol>toluene>dichloromethane. The Cu–Mn/Al catalyst was found to be the most active and selective catalyst in ethanol oxidation. In oxidation of dichloromethane, the Pt–Pd/Al–Ce catalyst with 0.10wt% Pt+Pd was the most active, while the most selective one (giving the highest HCl yield) was the Pt–Pd/Al catalyst containing 0.24wt% Pt+Pd. In toluene oxidation, the Pt–Pd/Al catalyst with 0.24wt% Pt+Pd possessed the highest activity; the selectivity to CO2 was 100% for all investigated catalysts. Obtained results showed that the performance of commercial catalysts in laboratory scale tests can be different from that declared by catalyst supplier. A possible difference in catalytic performance at industrial and laboratory scale should be taken into account when industrial catalysts are used in laboratory scale tests.